Organic and mineral fertilization in castor bean plants - Ferreira, Rosinaldo de Sousa; Maia Júnior, Sebastião de Oliveira; Lima, Alex Serafim de; Sousa, Caio da Silva; Alves, Jackson de Mesquita; Pedroza, Juarez Paz (Acta Iguazu, 2019)
The increase in the castor bean cultivation has raised the interest in quantitatively and qualitatively improving the productive characteristics of the crop, and this has required the use of new strategies in cultivation systems, as adequate management with organic and mineral fertilization. Thus, the objective of this work was to evaluate growth and productive characteristics of castor bean, under organic and mineral fertilization with castor cake and nickel. The experiment was carried out in a protected environment, in the Empresa Brasileira de Pesquisa Agropecuária, located in the city of Campina Grande, PB. The factorial was used 4x4, with four concentrations of castor cake (0.0, 1.0, 2.0 and 3.0 t ha-1), and four concentrations of nickel (0.0, 4.0, 8.0 and 12.0 mg L-1), with four replications. The castor cake increased plant height, stem diameter, leaf area and dry mass of stem by maximum concentration of 2.56 t ha-1. The dry mass of leaves and roots increased to 3 t ha-1. There was interaction between castor cake and nickel concentrations for racemes length, number of fruits and number of seeds. The castor cake in the concentration of by 2.56 t ha-1 favors the growth of castor plants, so that the increase doesn’t limit the dry mass production of leaves and roots, number of fruits and seeds.